Nanowire transistors : physics of devices and materials in one dimension - Colinge, Jean-Pierre; Greer, Jim (Cambridge University Press, 2016)
From quantum mechanical concepts to practical circuit applications, this essential book presents a self-contained and up-to-date account of the physics and technology of nanowire semiconductor devices. --